Unique pattern of late gadolinium enhancement on cardiac magnetic resonance imaging in Duchenne muscular dystrophy - Madhusudan Ganigara; Bharti Sharma; Ravi Babu Komalla; Suman Y Vyas; Gopichand Mannam; Nitin Krishna Rao (Wolters Kluwer Medknow Publications, 2016)
Cardiomyopathy is an important cause of morbidity and mortality in patients with Duchenne muscular dystrophy (DMD). Early recognition of myocardial involvement and initiation of therapy are important for improved outcomes. Cardiac magnetic resonance imaging (CMR) is a sensitive tool in early detection of myocardial fibrosis in these children.